The Effect of Exercise Intensity on Pancreatic and Liver GLUT-2 Expression in High Fructose-Fed Mice - Tantia Dewi Harianto; Bagas Trio Pamungkas; Purwo Sri Rejeki; Citrawati Dyah Kencono Wungu; Joni Susanto; Nabilah Izzatunnisa; Tri Hartini Yuliawati; Shariff Halim; Adi Pranoto (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Excessive high fructose corn syrup (HFCS) leads to metabolic disorders characterized by decreased expression of pancreatic GLUT-2 and increased expression of liver GLUT-2. Exercise is reported to be a non-pharmacological therapy to improve metabolic disorders. This study aims to compare differences in exercise intensity to changes in pancreatic and liver GLUT-2 expression in mice induced by high fructose. A total of 36 male mice (Mus musculus), weighing 20-30 grams, 8-week-old, were randomly divided into 4 groups: C (Control; n = 9), G1 (light intensity swimming exercises; n = 9), G2 (moderate intensity swimming exercises; n = 9), and G3 (heavy intensity swimming exercises; n = 9). All groups were given 30% fructose solution orally (oral ad libitum) for 8 weeks. Meanwhile, swimming exercise was given out 3×/week for 8 weeks with three different intensities. Pancreatic and liver GLUT-2 expression was measured using immunohistochemistry (IHC) and the results of pancreatic and liver GLUT-2 expression measurements were evaluated using the Immunoreactive Score (IRS). The analysis of body weight using one-way ANOVA followed by Tukey's Honest Significant Difference (HSD) post hoc test indicates that G2 significantly reduces weight compared to C, G1, and G3 (p ≤ 0.05). Statistical analysis was done using the Kruskal-Wallis non-parametric test and followed up with the Mann-Whitney U Test with a significant level of 5%. The data showed that G2 significantly increased expression of pancreatic GLUT-2 and decreased expression of liver GLUT-2 compared to C, G1, and G3 (p ≤ 0.05). In conclusion, moderate-intensity exercise has the most optimal effect in increasing the expression of pancreatic GLUT-2 and decreasing the expression of liver GLUT-2.